Food choice, embodied knowledge and circumscribed agency: factors influencing adolescent girls' and boys' dietary practices in three states in northern Nigeria - Abigail Conrad; Akriti Singh; Sharmila Mysore; Stanley Nwosu; Michael Daniel Eveshoyan; Usman Ibraheem (Cambridge University Press, 2024)
Abstract Objective: The objective of this study was to explore adolescent dietary practices, related norms and acceptable communication platforms in northern Nigeria to inform future nutrition project design. Design: This was a qualitative formative research study. We used purposive sampling and conducted thirty focus group discussions with male and female adolescents aged 10-14 and 15-19 years (n 180) and six with adult influencers (n 36). We also administered a 24-h dietary recall with the adolescents using the Diet Quality Questionnaire. Setting: The study was conducted in urban and rural areas in three states in northern Nigeria. Results: Adolescents reported consuming six nutritious food groups the previous day on average. However, there was a wide disparity and only half consumed all five recommended food groups. Adolescents' food choices were influenced by perceptions of the functional and physical benefits of nutritious foods and preferences for satisfying foods. Diverse foods were available in the food environment, but affordability constrained access to nutritious foods. Limited access to income and gender norms constrained adolescent agency over food choice. Girls, particularly those who were pregnant, had less agency related to food than boys. Adolescents thought that peers should be reached through group discussions, radio and phones, among other communication platforms. Conclusions: Adolescents consumed relatively diverse diets. Adolescent food choice was influenced by their embodied experience and knowledge related to nutrition and taste, home food environment and circumscribed agency. Opportunities exist to support healthy diets for adolescents by strengthening adolescents' embodied knowledge, food environments and social support.